Towards a mechanistic understanding of carbon stabilization in manganese oxides - Johnson, Karen (Nat Commun, 2015)
Minerals stabilize organic carbon (OC) in sediments, thereby directly affecting global climate at multiple scales, but how they do it is far from understood. Here we show that manganese oxide (Mn oxide) in a water treatment works filter bed traps dissolved OC as coatings build up in layers around clean sand grains at 3%w/wC. Using spectroscopic and thermogravimetric methods, we identify two main OC fractions. One is thermally refractory (>550 °C) and the other is thermally more labile (<550 °C). We postulate that the thermal stability of the trapped OC is due to carboxylate groups within it bonding to Mn oxide surfaces coupled with physical entrapment within the layers. We identify a significant difference in the nature of the surface-bound OC and bulk OC . We speculate that polymerization reactions may be occurring at depth within the layers. We also propose that these processes must be considered in future studies of OC in natural systems.